Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Sebagai Pelayanan Publik - Solechan Solechan (Administrative Law and Governance Journal, 2019)
Abstract The purpose of this research is to find out how the role of the health insurance provider (BPJS) as a form of public service in Indonesia. Research is a normative study with a comparative approach. The research results show that public services or public services can be defined as all forms of services, both in the way of goods and services which in principle are the responsibility and are carried out by government agencies at the central, regional and in the environment of state-owned enterprises or business entities Regional Owned. One of them is the Social Security Organizing Agency is a legal entity to organize social security programs to ensure all people can meet the basic needs of a decent life. BPJS is held based on the principles of humanity, benefits, and social justice for all Indonesian people with the aim of realizing the fulfillment of the basic needs of a decent life for every Indonesian people who have become basic human rights. Keywords: Social Security Organizing Agency, Health, Public Services Abstract Penelitian ini bertujuan utnuk mengetahui bagaimanakah peran badan penyelenggara jaminan sosial (BPJS) kesehatan sebagai salah satu bentuk pelayanan publik di Indonesia. Penelitian merupakan penelitian normatif dengan pendekatan perbandingan. Hasil penelitian menujukan bahwa Pelayanan publik atau pelayanan umum dapat didefinisikan sebagai segala bentuk jasa pelayanan, baik dalam bentuk barang maupun jasa yang pada prinsipnya menjadi tanggung jawab dan dilaksanakan oleh Instansi Pemerintah di Pusat, di Daerah, dan di lingkungan Badan Usaha Milik Negara atau Badan Usaha Milik Daerah. Salah satunya adalah Badan Penyelenggara Jaminan Sosial merupakan sebuah badan hukum untuk menyelenggarakan program jaminan sosial untuk menjamin seluruh rakyat agar dapat memenuhi kebutuhan dasar hidup yang layak. BPJS diselenggarakan berdasarkan asas kemanusiaan, manfaat, dan keadilan sosial bagi seluruh rakyat Indonesia dengan tujuan untuk mewujudkan pemenuhan kebutuhan dasar hidup yang layak bagi setiap rakyat Indonesia yang sudah menjadi hak dasar manusia. Kata Kunci: Badan Penyelenggara Jaminan Sosial, Kesehatan, Pelayanan Publik